2015
DOI: 10.1002/aic.15046
|View full text |Cite
|
Sign up to set email alerts
|

Length to diameter ratio of extrudates in catalyst technology I. Modeling catalyst breakage by impulsive forces

Abstract: Natural or forced catalyst extrudate breakage is an important phenomenon during catalyst manufacture. Here, a twoparameter model for predicting the reduction in the length to diameter ratio of catalyst extrudates due to breakage by impulsive forces as experienced in a laboratory drop test is developed. Part II will show how both parameters can be correlated with the strength of the extrudates and the severity of the drop test. For breakage by impulsive forces, the model reveals that extrudates are reduced in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…To summarize, if a bed of extrudates is loaded in the bulk crush strength test and a stress P is applied, then the extrudates will break throughout the entire bed under the applied stress P to an average value given by Eq. (8). It is clear from the equation of the aspect ratio as a function of Be r that a bed with a starting aspect ratio F 0 has a critical pressure P c it can withstand given by:…”
Section: Balance Of the Rupture Force With A Fixed-bed Static Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, if a bed of extrudates is loaded in the bulk crush strength test and a stress P is applied, then the extrudates will break throughout the entire bed under the applied stress P to an average value given by Eq. (8). It is clear from the equation of the aspect ratio as a function of Be r that a bed with a starting aspect ratio F 0 has a critical pressure P c it can withstand given by:…”
Section: Balance Of the Rupture Force With A Fixed-bed Static Loadmentioning
confidence: 99%
“…Both the single‐pellet crush strength test and the bulk crush strength test are important aspects in understanding catalyst mechanical properties. When considering practical catalyst breakage, there also exists a need to determine the bending strength of the catalyst, and reference is given to Li et al , Staub et al and Beeckman et al , . The bending strength of the catalyst is characterized by the Euler‐Bernoulli modulus of rupture and is typically obtained in a three‐point bending test.…”
Section: Introductionmentioning
confidence: 99%
“…Beeckman has shown that also a second asymptotic aspect ratio exists. It is observed after just one drop, when the starting aspect ratio is sufficiently large.…”
Section: Theoreticalmentioning
confidence: 99%
“…The development of the finite difference modeling of the drop test has been described in detail by Beeckman. The authors show that two asymptotic aspect ratios exist for collision against a surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation